Application of k0-method of neutron activation analysis for determination of trace elements in various mineral samples: a review - Jacimovic, Radojko; Stafilov, Trajce; Stibilj, Vekoslava; Taseska, Milena; Makreski, Petre (Society of Chemists and Technologists of Macedonia, 2015)
Various trace elements in different types of arsenic (orpiment, As2S3; realgar, As4S4; lorandite, TlAsS2), antimony (stibnite, Sb2S3), copper (brochantite, Cu4SO4(OH)6; chalcanthite, CuSO4·5H2O; chalcopyrite, CuFeS2; covellite, CuS; native copper, Cu) and iron based geological materials (hematite, Fe2O3; pyrite, FeS2; chalcopyrite, CuFeS2) were determined using k0-method of neutron activation analysis (k0-NAA) in both forms: instrumental (k0-INAA) and radiochemical (k0-RNAA). In order to avoid interferences from the matrix element (As, Sb, Cu and Fe), various procedures were applied for its removal. Elimination of the matrix element enabled investigation from 35 to 47 trace elements in the samples using short (up to few minutes) and long (up to 20 hours) irradiations in typical irradiation channels of TRIGA reactor. The minerals were collected from various localities within the Republic of Macedonia, except covellite, which was obtained from Bor, Serbia.